Pemetaan Tren Penelitian Manajemen Krisis: Analisis Bibliometrik dengan VOSviewer - Iswardhani, Indri (Baashima : Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2025)
This study examines the trends and primary research focuses in the field of crisis management using bibliometric methods supported by VOSviewer software. The analysis was conducted on 493 scholarly articles retrieved from Google Scholar with the keyword "crisis management." The results indicate a total of 3,096 citations, averaging 774 citations per year and 6.28 citations per article, with an h-index of 25 and a g-index of 46, reflecting the significant relevance and impact of this field in academic literature. Mapping of key terms identified 13 main terms grouped into six thematic clusters, including Good Corporate Governance (GCG), Corporate Social Responsibility (CSR), digital transformation, human resource management, economic crisis, and responses to the Covid-19 pandemic. Data visualization shows a shift in research focus from pandemic response to the challenges and opportunities in the digital era, emphasizing governance and social responsibility as key crisis mitigation strategies. This study provides important empirical contributions to the development of crisis management theory and practice, as well as practical implications for organizations to enhance preparedness in facing crises. Future research is recommended to adopt mixed methods and broaden the scope of data sources to gain a more comprehensive understanding.